Optimization and demonstration of two types of spring-roll dielectric elastomer actuators for minimally invasive surgery - Wang, HaoChen; Cui, Saihui; Niu, Fuzhou (Frontiers in Bioengineering and Biotechnology, 2022)
Resulting from the restricted size of incisions and confined surgical space, the existing rigid and slender minimally invasive surgery (MIS) instruments are inefficient in providing an optimum articulation to handle certain MIS tasks. Thus, developments of novel articulating actuators are of urgent requirement. In this paper, with the aim to enhance the flexibility and maneuverability of surgical instruments in diverse MIS scenarios, two types of spring-roll dielectric elastomer (DE) actuators, namely linear-type and bending-type, are proposed. The actuators’ parameters were optimized and calibrated using a novel step-by-step procedure, based on the characterization and modeling of DE material (VHB 4905). Critical design factors including dimensions of the core spring, the pre-stretch ratio of the DE, and the excitation level of the actuator were identified, while the boundary conditions for the modeling of the actuator were derived from the requirements of MIS applications. The DE actuators' deformation behavior and force response were analyzed both theoretically and experimentally, and the results from the two approaches were in good agreement. The linear-type actuator could achieve a maximum strain of 29% and a blocking force up to 5.05 N, while the bending-type actuator could achieve angulation over 70° and a blocking force of up to 0.22 N. The proposed actuators are lightweight, compact, and cost-effective, which could provide novel design inspiration for MIS instruments.